Interpreting the circulation of educational discourse across space: searching for new vocabularies - Beech, Jason (2015)
This article argues that certain established vocabularies that are used to interpret the circulation of educational discourse and its transformation in different settings have significant limitations to capture the complexity inherent to new geographies of power/knowledge in education and that, consequently, we need to develop new concepts to analyse the movement of educational discourses across space. After a critique of concepts such as ‘transfer’ and ‘policy borrowing’, we offer an alternative kind of approach by using Actor-Network Theory (ANT) to briefly analyse Conectar Igualdad, a program in Argentina that distributes one computer per student in secondary schools. It will be shown how the use ANT can make certain connections visible that would not be so noticeable using the established vocabularies discussed above.